2019
DOI: 10.1002/icd.2156
|View full text |Cite
|
Sign up to set email alerts
|

“Let's make a place where giants live!”: Children's communication during play with siblings and friends from early to middle childhood

Abstract: The present study examined children's co‐construction of shared meanings and internal state language during play with their sibling and friend from early to middle childhood. Sixty‐five 4‐year‐old children (T1) and 46 7‐year‐old children (T2) were observed in the home during two free play sessions with a sibling and with a friend at both time points. Shared meaning strategies during social play (e.g., extensions and positive responses) and during pretend enactment were coded. Shared meaning strategies were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 53 publications
2
8
0
Order By: Relevance
“…Clarification strategies were also employed to sustain connectedness in line with the literature (Göncü, 1993;Howe et al, 2005;Leach et al, 2015Leach et al, , 2019b along with a trend for positive responses. Clarifications may elicit positive responses and the two behaviours complement one another, thus suggesting reciprocal turn-taking is critical aspect of play communications (Garvey, 1990;Göncü, 1993).…”
Section: Children's Shared Meanings Strategies and Connectednessmentioning
confidence: 99%
See 4 more Smart Citations
“…Clarification strategies were also employed to sustain connectedness in line with the literature (Göncü, 1993;Howe et al, 2005;Leach et al, 2015Leach et al, , 2019b along with a trend for positive responses. Clarifications may elicit positive responses and the two behaviours complement one another, thus suggesting reciprocal turn-taking is critical aspect of play communications (Garvey, 1990;Göncü, 1993).…”
Section: Children's Shared Meanings Strategies and Connectednessmentioning
confidence: 99%
“…That is, are children's play communications organized in a coordinated, reciprocal fashion or are they seemingly disorganized? To begin, to answer this question, Leach et al (2019b) first investigated children's ability to co-construct sustained connected play sequences from early to middle childhood with their siblings and friends; connectedness was defined as sequences characterized by continuous, socially coordinated, and mutually constructed verbal exchanges (Fogel, 1993;Harrist & Waugh, 2002). Leach et al reported focal children's ability to co-construct and sustain connected play sequences with both their sibling and friend were associated with a positive emotional tone of their interactions; they were also increasingly cooperative from early to middle childhood.…”
Section: Developing Connectedness Communications During Playmentioning
confidence: 99%
See 3 more Smart Citations